Dampak Kejadian Banjir Terhadap Ketersediaan Pangan Di Kabupaten Lampung Selatan - Rika Agustina; Zainal Abidin; Slamet Budi Yuwono; Samsul Bakri (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
South Lampung District is one of the food barns for Lampung Province. The agricultural sector can be affected by changes in rainfall, especially in the food crop agricultural sector, which will affect the availability of food production. This study aims to identify the contribution of flood events, food availability and factors that directly and indirectly influence food availability in South Lampung District. The data used is secondary data. Identification of flood events based on information data from the National Disaster Management Agency (BNPB), food availability is calculated based on the Food Material Balance guidelines from the Food Security Agency and analysis of direct and indirect effects using path analysis. The study suggests that flooding mostly occurs in Palas, Penengahan, Candipuro, and Sidomulyo Districts In terms of rice production in 2019, six sub-districts experienced deficit in food production with an average decline of 33.9 percent due to drought. The variable of harvested area has a direct and indirect effect on food availability with the intervening variable the amount of production.